Recurrent Acute Pancreatitis Secondary to a Duodenal Duplication Cyst in an Adult. A Case Report and Literature Review - Nikolaos S Salemis; Christos Liatsos; Michail Kolios; Stavros Gourgiotis (Canadian Journal of Gastroenterology)
Duodenal duplication cysts are rare congenital abnormalities that are most commonly diagnosed in infancy and childhood. However, in rare cases, the lesion can remain asymptomatic until adulthood. An extremely rare case of a previously healthy adult patient with recurrent acute pancreatitis, who was diagnosed with a duodenal duplication cyst is presented. At laparotomy, a duplication cyst measuring 4.8 cm × 4 cm × 4 cm was found adjacent to the ampulla of Vater. A partial cyst excision and marsupialization into the duodenal lumen was performed. The patient is healthy and asymptomatic four years after surgery. The present case illustrates the necessity of considering a duodenal duplication cyst in the differential diagnosis of recurrent acute pancreatitis in previously healthy adults.